Bioinspired nanomaterials for energy and environmental applications. - Pandikumar, A. (Materials research foundations., 2022)
The book presents recent advances in the synthesis of bioinspired nanomaterials and their applications in areas such as photocatalysis, electrocatalysis and photoelectrocatalysis, supercapacitors and solar cells.